Desain Alat Penggerak Fuse Carrier pada Fuse Cut Out untuk Jaringan Tegangan Menengah - Bahtiar, Ade Candra Bahtiar; Suryono; Wahjono, Endro (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
Fuse Cut Out (FCO) is a separation device in medium voltage networks, FCO removal is done by separating the top contact with the fuse carrier. How to remove the fuse carrier in general still uses a manual method with special equipment, namely a 20KV telescopic stick. The use of telescopic sticks is very time consuming and prone to leakage of insulation which affects work safety. In this study, the release of the fuse carrier was carried out with a remote control as a command to release and enter the fuse carrier.  Testing of this tool is carried out at a voltage of 223 Volts AC. The remote control design is able to provide a command signal with a maximum distance of 21 m in real time conditions. The mechanical construction is adapted to the standard clearance distance in the medium voltage network and the results of mechanical manufacturing of the upper contact with the fuse carrier release distance of 207 mm and the upper contact with the pneumatic actuator of 200 m, the compressed air source uses 5bar. The average success was 88.8% Phase R, 77.7% Phase S, 77.7% Phase T. The construction of the fuse carrier drive tool in this study is used in the release of FCO so that release and entry require faster time and optimise work safety.